1976
DOI: 10.1080/17450397609423240
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen zur Sezernierung endogener Aminosäuren in den Verdauungstrakt und zur Aminosäurenresorption beim Schwein

Abstract: A trial was performed with 2 fistula pigs (each with 2 fistulas, one located about 30 cm below the pyloric orifice and the other at the end of the small intestine). Animal A received a casein diet containing 14% crude protein for a period of 2 weeks before the tracer amino acid was administered. Animal B received the same diet for a period of 10 days and was then fed a diet (at the same protein level) containing gluten as sole protein source. The two tracer amino acids, 14C-U-L-leucine and 3H-4,5-(N)-L-lysine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…It has been shown that amino acids in these secretions are poorly absorbed from the intestine. 25 The endogenous amino acid output measured in this trial was similar to that recorded by other workers.6Jc28 Endogenous nitrogenous losses have been shown to vary only very slightly with bodyweight changes. 16,29 Consequently, feeding PF1 and PF2 at different liveweights was not likely to have a large influence on endogenous output.…”
Section: 5'supporting
confidence: 84%
See 1 more Smart Citation
“…It has been shown that amino acids in these secretions are poorly absorbed from the intestine. 25 The endogenous amino acid output measured in this trial was similar to that recorded by other workers.6Jc28 Endogenous nitrogenous losses have been shown to vary only very slightly with bodyweight changes. 16,29 Consequently, feeding PF1 and PF2 at different liveweights was not likely to have a large influence on endogenous output.…”
Section: 5'supporting
confidence: 84%
“…The DM, crude protein (Nx6. 25) and crude fibre contents of the test diets are shown in Table 2. The values of crude fibre concentration for the protein-free diets show that either there was incomplete recovery of the purified cellulose during analysis, or that impurities were present.…”
Section: Resultsmentioning
confidence: 99%
“…This study (Sauer et al 1977) was done with diets ranging in crude fibre content from 39 to 108 g/kg. The predominance of non-essential amino acids contained in endogenous secretions recovered at the terminal ileum is also supported by the work of Zebrowska et al (1976). Even after ingestion of dietary protein, the abundance of non-essential amino acids in endogenous matter appearing at the terminal ileum seems to persist (Taverner et al 1981).…”
Section: Discussionmentioning
confidence: 83%
“…A greater apparent absorption of N from the hydrolyzed proteins than the intact proteins occurred in the duodenum and jejunum. There were no differences in the lower parts of the digestive tract suggesting that all readily-digestible protein had been digested and that the slower digestion of the less-digestible fractions including endogenous secretions (Zebrowska et al 1976) occurred in the ileum, caecum and large intestines.…”
Section: Discussionmentioning
confidence: 97%